Environmental Triggers Associated With Empty Nose Syndrome Symptoms: A Cross-Sectional Study. (July 2019) - Manji, Jamil; Patel, Vishal S.; Nayak, Jayakar V.; Thamboo, Andrew
Objectives: Empty nose syndrome (ENS) is thought to have multiple etiologies, one of which is a postsurgical phenomenon resulting from excessive loss of nasal tissues, particularly the inferior turbinate. Given that the inferior turbinate is instrumental in maintaining nasal homeostasis in different environments, it is believed that ENS symptoms arise only in more arid regions of the world. The aim of this study was to recruit an international population of individuals with ENS to investigate the association of local climate factors on the incidence and severity of ENS-specific symptoms. Methods: A cross-sectional study was performed of individuals from an international ENS database. ENS status was determined on the basis of a positive ENS questionnaire score (Empty Nose Syndrome 6-Item Questionnaire) and sinus computed tomographic imaging with supporting medical documentation. Participants completed a survey encompassing demographic, geographic, and symptom indicators. Climate variables were collected from global climate databases. Participant location was classified according to the Köppen-Geiger climate system. Pearson correlation analysis was performed using α = 0.05 to determine significance. Results: Fifty-three individuals with ENS were included. Participants were distributed across 5 continents and 15 countries (representing 4 distinct Köppen-Geiger zones). Although local climate factors varied significantly within this cohort, no significant association was found between Empty Nose Syndrome 6-Item Questionnaire symptom severity and these climate factors. However, most study participants reported exacerbation of their ENS symptoms in response to dry air (94%), air conditioning (64%), changes in season and weather (60%), and transitioning between indoors and outdoors (40%). This suggests that everyday local environmental factors may influence the well-being of these patients more than global, climate-level shifts. Conclusions: ENS symptom severity does not appear to be related to climate or geographic factors. These findings deviate from the traditional dogma that ENS is experienced only in arid regions (or precluded in humid regions) and highlight the importance of recognizing this condition independent of geographic location.